Pengaruh Likuiditas Terhadap Profitabilitas Pada Bank Umum Syariah di Indonesia Periode 2015-2020 - R. Azky Afina Fasa; Ade Ali Nurdin; Fifi Afiyanti Tripuspitorini (Jurusan Akuntansi Politeknik Negeri Bandung, 2022)
This study is expected to determine and analyze the effect of liquidity on profitability at Islamic Commercial Banks (BUS) in Indonesia for the 2015-2020 period. The dependent variable used in this study is the profitability of Islamic commercial banks as proxied by Return on Assets (ROA) when the independent variables in this study are liquidity proxied by the Financing to Deposit Ratio (FDR), Liquid Assets to Total Assets (LATA) and Liquid Assets to Deposits (LAD). This study uses a population of Islamic Commercial Banks (BUS) in Indonesia then the sample used is purposive sampling with 10 Islamic Commercial Banks selected according to predetermined criteria. The data analysis method used was panel data with using EViews9 software. The results of this study indicate partial that LATA has a significant effect on ROA because it has a probability value < 0.05, namely 0.0241, while LAD and FDR have no significant effect on ROA because they have probability values ​​> alpha 0.05, namely 0.6523 and 0.5704. Simultaneously, the three independent variables have a significant effect on the dependent variable.